(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2025)
The present research has the objective of investigating the relations that can be established between the language of costume and the aesthetic of the grotesque. To do so, I have developed Garatujas Animalescas, a series of costumes created inspired by animals that are considered disgusting. For the development of that project, I did a literary review in order to understand the theoretical proposals about the aesthetic of the grotesque, as well as a search to know and identify grotesque costumes in different contexts. Next, I report the process of creation of the garatuja inspired by the fly (Musca domestica) as well as the obstacles and the solutions found. Lastly, I question the necessity of a show in order to develop costumes.